High Waist to Hip Ratio as a Risk Factor for Ischemic Stroke Patients Admitted in a Tertiary Care Hospital (Bangladesh Journal of Anatomy, 2011)
Context: Stroke is a problem now days. The purpose of this study is to see the association of high waist-to-hip ratio with ischemic stroke and also to see the correlation with other risk factors of ischemic stroke. Study type: Hospital based cross sectional descriptive study Methods: It is a study conducted on purposively selected (non probability) hospitalized patients who had been admitted into neuromedicine ward of Chittagong Medical College Hospital (CMCH), Chittagong prooved during a period of 6 months extending from 1st January 2009 to 31st June 2009. 50 cases with CT scan prooved ischemic stroke of brain were interviewed and examined and had measurements of waist and hip circumference and waist to hip ratio (WHR) were calculated. Results: 64% of the ischemic stroke patient had abnormal WHR. The correlation with other risk factors showed that 90% of ischemic stroke patient had other co-morbidity. Among them 76% patient had hypertension, 38% patients had history of smoking, 16% patients had diabetes mellitus and 12% patients had dyslipidaemia. Conclusion: The results reveal that high waist to hip ratio might have an association with ischemic stroke. Key words: Ischemic stroke; Waist-to-Hip Ratio (WHR). DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8145 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 30-34